Tannins as Hemostasis Modulators - Natalia Marcińczyk; Anna Gromotowicz-Popławska; Michał Tomczyk; Ewa Chabielska (Frontiers Media S.A., 2022)
The hemostasis system is often affected by complications associated with cardiovascular diseases, which results in thromboembolic events. Compounds of plant origin and plant extracts are considered as a promising source of substances that could modulate the functioning of the hemostasis system and thus reduce the risk of thromboembolism. Among them, tannins, which are plant-origin compounds with potential effects in hemostasis, deserve a special mention. This paper describes the hemostasis-modifying ability of three groups of tannins, namely ellagitannins, gallotannins, and procyanidins. The review highlights the desirable as well as undesirable influence of tannins on specific components of hemostasis, namely platelets, coagulation system, fibrinolysis system, and endothelium, and the multidirectional effect of these compounds on the thrombotic process. Studies performed under normal and pathological conditions such as diabetes or hypercoagulation are described, and the pathophysiology-dependent action of tannins is also highlighted. Most of the studies presented in the paper were performed in vitro, and due to the low bioavailability of tannins more studies should be conducted in the future to understand their actual activity in vivo.